PENGARUH RASIO KEUANGAN TERHADAP DIVIDEND PAYMENT PADA PERUSAHAAN YANG TERDAFTAR DI BEI - HANDI HANDI; RUTJI SATWIKO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The aim of this research is to determine the effect of profitability, liquidity, leverage, firm size, earning per share, and growth on dividend payout ratio.This research uses data from 66 non-financial companies listed on the Indonesia stock exchange (IDX) from the period 2011 to 2014. Data for this study are selected using several criteria and using purposive sampling method. The method of data management involves hypothesis testing in multiple linear regression. The results of this research show that profitability, earning per share, and growth have a significant effect on dividend payout ratio, on the other hand liquidity, leverage, and firm size, do not have a significant effect on dividend payout ratio.